Notice of Retraction Ethnic vs Math: The Secret inside Borobudur Temple, Indonesia - Wanda Nugroho Yanuarto (Journal of Education and Learning (EduLearn), 2017)
Notice of Retraction-----------------------------------------------------------------------After careful and considered review of the content of this paper by a duly constituted expert committee, this paper has been found to be in violation of UAD-IAES's Publication Principles.We hereby retract the content of this paper. Reasonable effort should be made to remove all past references to this paper.The presenting author of this paper has the option to appeal this decision by contacting edulearn@journal.uad.ac.id.-----------------------------------------------------------------------Mostly in Eastern religions, particularly in Indonesia the ancient Imperial cults of Borobudur temple as Buddhism, ritually celebrate their beliefs as a congregation where prayer and religious addresses are a communal activity. This culture is interesting to study whether building a place of worship is built on the cultural elements or there is a correlation with formula or complicated calculations about how the building is erected . The mathematical study for Borobudur’s architectural design has once related to answer the question about the metric system used by ancient Javanese to build such giant buildings with good measurement. Fractal dimension is calculated by using the cube counting method and found that the dimension is , which is laid between the two-dimensional plane and three dimensional space. The applied fractal geometry and self-similarity of the building is emerged as the building process implement the metric rules, since there is no universal metric standard known in ancient traditional Javanese culture thus the architecture is not based on final master plan. The paper also proposes how the hypothetical algorithmic architecture might be applied computationally in order to see some experimental generations of similar building. The paper ends with some conjectures for further challenge and  insights related to fractal geometry in Javanese traditional cultural heritages.